2018
DOI: 10.1155/2018/1862401
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antibacterial Activity of Selected Medicinal Plants in the Traditional Treatment of Skin and Wound Infections in Eastern Ethiopia

Abstract: Background External infections involving the skin and wound are the most frequent complications affecting humans and animals. Medicinal plants play great roles in the treatment of skin and wound infections. This study was aimed to evaluate the in vitro antibacterial activity of crude methanolic extracts of nine medicinal plants. Methods Agar well diffusion and broth dilution methods were used to determine the antibacterial activity of nine Ethiopian plants against four bacterial species including Staphylococcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 23 publications
0
28
0
1
Order By: Relevance
“…For example, tannins produce antibacterial activity by inactivating numerous enzymes, microbial adhesion, and cell envelope transport proteins [35]. Other active components like saponins have been reported to possess antibacterial activity, which could be attributed to their ability to form a complex with extracellular proteins, soluble proteins, and bacterial cell walls [55]. Other previous antibacterial studies also proved that the presence of these secondary metabolites has an important role in the inhibition of bacterial growth [21,54,55].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, tannins produce antibacterial activity by inactivating numerous enzymes, microbial adhesion, and cell envelope transport proteins [35]. Other active components like saponins have been reported to possess antibacterial activity, which could be attributed to their ability to form a complex with extracellular proteins, soluble proteins, and bacterial cell walls [55]. Other previous antibacterial studies also proved that the presence of these secondary metabolites has an important role in the inhibition of bacterial growth [21,54,55].…”
Section: Discussionmentioning
confidence: 97%
“…According to Fentahun et al, the chloroform leaf extract of B. antidysenterica has showed highest (11 mm) zone of inhibition [22]. Other results done on different plants against P. aeruginosa showed that the zone of inhibition was ranging between 9 and 21 mm [23,32,35,55,56]. This may indicate that the root extract of B. antidysenterica has been promising activity against P. aeruginosa and important to tackle diarrhoea secondary to chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The method was performed according to that previously reported. 17 A sterilized Muller Hinton Agar was poured into sterile plates, after solidification, 100 µl of fresh culture of Enterobacter strains (0.5 MacFarland) were swabbed on the respective plates. Standard wells were made on the agar plate.…”
Section: Well Diffusion Methodsmentioning
confidence: 99%
“…This shows that 10 ppm concentration of the extract can inhibit Pseudomonas fluorescens bacteria. The low absorbance value indicated no bacterial growth or inhibited bacterial growth [21]. The high and low concentrations of extract that causes differences in the MIC value, so it can be seen there is a presence or absence of bacterial growth [22].…”
Section: Minimum Inhibitory Concentration (Mic)mentioning
confidence: 99%